Independence and preventive imprisonment - Álvarez Yrala, Edwar (2015)
The New Criminal Procedure Code of 2004 provides an extensive protection in terms of fundamental rights; however, a new obstacle for the proper administration of justice has surfaced involving the judge, who is constantly being affected in its finaldecision by the media.The author of this article discusses this problem from the field of preventive imprisonment, focusing on current cases and doctrine. In addition, the author makes an analysis and classification of judges based on their way of making choices, showing a discouraging picture of the situation.